Od žive debate do zapisane besede - Gašparič, Jure (Zgodovinski časopis, 2016)
The verbatim records of parliamentary sessions are on account of various reasons (amount of data, broad subject matter, "paradigmatic" provocativeness of the material) one of the more attractive sources in historiography. Additionally, they are considered to be an extraordinarily reliable source. However, the authors point to the fact that verbatim records of parliamentary sessions are the result of work done by note takers, who often faced many problems. What were they to do if they could not hear the member of parliament, how to deal with exclamations from the back of the session hall, with words spoken in dialect, how is one to put down incorrect terms? In the search of answers to these questions, we focus on the emergence of verbatim records of parliamentary sessions in parliaments in the territory of present-day Slovenia.
Keywords: Habsburg Monarchy; habsburška monarhija; Jugoslavija; Kingdom of Yugoslavia; Kraljevina SHS; parlament; politični govori; primary source; Slovenia; Slovenija; stenografi; stenografski zapisi; Yugoslavia; zgodovinski viri